2022
DOI: 10.1073/pnas.2115857119
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the foreign body response to implantable medical devices by inflammasome inhibition

Abstract: Significance Implantable electronic medical devices (IEMDs) are used for some clinical applications, representing an exciting prospect for the transformative treatment of intractable conditions such Parkinson’s disease, deafness, and paralysis. The use of IEMDs is limited at the moment because, over time, a foreign body reaction (FBR) develops at the device–neural interface such that ultimately the IEMD fails and needs to be removed. Here, we show that macrophage nucleotide-binding oligomerization do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 61 publications
5
30
1
Order By: Relevance
“…5). RR can be particularly advantageous for potent drugs where accurate dosing and a rapid time to functional effect are important, or macro-drugs such as proteins, where convective flow enhances diffusion-based flux, principally governed by molecular weight and concentration gradient 33,34 . Convection-enhanced delivery has been successfully used to improve distribution of chemotherapy in deep brain tumour targets, albeit with modest clinical outcomes 26,27,32,63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). RR can be particularly advantageous for potent drugs where accurate dosing and a rapid time to functional effect are important, or macro-drugs such as proteins, where convective flow enhances diffusion-based flux, principally governed by molecular weight and concentration gradient 33,34 . Convection-enhanced delivery has been successfully used to improve distribution of chemotherapy in deep brain tumour targets, albeit with modest clinical outcomes 26,27,32,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Local targeted delivery can reduce off-target effects but may still adversely affect the underlying tissue or interfere with the mechanism of action of the implantable device. For example, local delivery of dexamethasone can mitigate the FBR, but not without suppressing underlying tissue regeneration 33 . Furthermore, the effect of long-term immunosuppression on the behaviour and secretome of cell-based therapeutics is unclear.…”
mentioning
confidence: 99%
“…Barone et al. ( 2022 ) combining a NLRP3 inhibitor (MCC950) with an implantable electronic medical devices, demonstrated the prevention of FBR without affecting tissue repair, in an in vivo nerve injury model. The authors showed that local inhibition of NLRP3 inhibits FBR, allowing full healing of the tissue, in comparison with the conventional treatments (dexamethasone), which also blocks FBR but at the same time impair tissue repair.…”
Section: The Potential Of the Inflammasome In Immunomodulationmentioning
confidence: 99%
“…[12][13][14][15] The second strategy utilizes pharmacologic means to reduce immune response through sustained release of drugs from coatings on implants. [16][17][18] However, both methods essentially focus on 'hiding' the implant from the body rather than truly integrating the implant with surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%